Fluid-dynamic assessment of sugarcane bagasse to use as feedstock in bubbling fluidized bed gasifiers - Perez, Nestor Proenza [UNESP]; Machin, Einara Blanco [UNESP]; Pedroso, Daniel Travieso [UNESP]; Antunes, Julio Santana [UNESP]; Silveira, Jose Luz [UNESP] (Elsevier B.V., 2014)
The fluid bed gasification of a sugarcane bagasse is a promising option for the large-scale production of fuel gas in order to increase the energetic efficiency of the sugar industry. A fluid-dynamic and thermodynamic assessment of the use of sugarcane bagasse as feedstock for a bubbling fluidized bed gasifier was performed. It was determined the required range of sugarcane bagasse particles sizes to permit the use this biomass as feedstock in bubbling fluidized bed gasifiers and the main fluidization parameters for the range of diameters proposed, with good agreements with the experimental values reported for the same Geldart's type of particles. A range of particle sized between 0.8 and 1.21 mm was suggested. The producer gas composition was modeled using air as gasification agent, obtaining a theoretical LHV of 4.56 MJ/Nm(3). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Biomass; Bubbling fluidized bed gasifier; Renewable energy; Sugarcane bagasse